Foundations of Music History - Dahlhaus, Carl 1928-1989; Robinson, J. B. (Cambridge Cambridge University Press, 1999)
This book is the first thoroughgoing study in any language of the philosophy of music history. Drawing on competing philosophies of history throughout the ages, from the Enlightenment to the French structuralists, from the German idealist tradition to Russian formalism, the late Carl Dahlhaus applies the thoughts of these various schools to the specialist requirements of music history and assesses their advantages and shortcomings. Special attention is given to an appraisal of whether Marxist critiques are still viable and where they stand in need of rethinking. For this English edition, the author provided an extensive annotated bibliography.
Keywords: Music history